The brink of peace : the Israeli-Syrian negotiations - Rabinovich, Itamar, 1942- (Princeton University Press, 1999)
A major casualty of the assassin's bullet that struck down Israeli Prime Minister Yitzhak Rabin was a prospective peace accord between Syria and Israel. For the first time, a negotiator who had unique access to Rabin, as well as detailed knowledge of Syrian history and politics, tells the inside story of the failed negotiations. His account provides a key to understanding not only U.S. diplomacy in the Middle East but also the larger Arab-Israeli peace process. During the period from 1992 to 1996, Itamar Rabinovich was Israel's ambassador to Washington, and the chief negotiator with Syria. In this book, he looks back at the course of negotiations, terms of which were known to a surprisingly small group of American, Israeli, and Syrian officials. After Benjamin Netanyahu's election as Israel's prime minister in May 1996, a controversy developed. Even with Netanyahu's change of policy and harder line toward Damascus, Syria began claiming that both Rabin and his successor Peres had pledged full withdrawal from the Golan Heights. Rabinovich takes the reader through the maze of diplomatic subtleties to explain the differences between hypothetical discussion and actual commitment. "To the students of past history and contemporary politics," he writes, "nothing is more beguiling than the myriad threads that run across the invisible line which separates the two." The threads of this story include details of Rabin's negotiations and their impact through two subsequent Israeli administrations in less than a year, the American and Egyptian roles, and the ongoing debate between Syria and Israel on the factual and legal bases for resuming talks. The author portrays all sides and participants with remarkable flair and empathy, as only a privileged player in the events could do. In any assessment of future negotiations in the Middle East, Itamar Rabinovich's book will prove indispensable
Keywords: Rabinovich, Itamar, -- 1942-; Israel -- Foreign relations -- Syria.; Syria -- Foreign relations -- Israel.; Arab-Israeli conflict -- 1993- -- Peace.; Israël -- Relations extérieures -- Syrie.; Syrie -- Relations extérieures -- Israël.; Conflit israélo-arabe -- 1993- -- Paix.; POLITICAL SCIENCE -- Government -- International.; POLITICAL SCIENCE -- International Relations -- General.; Arab-Israeli conflict -- Peace; Diplomatic relations; Israel; Syria; Since 1993; JSTOR-DDA; Israel -- Foreign relations -- Syria; Syria -- Foreign relations -- Israel; Arab-Israeli conflict -- 1993 -- Peace; Rabinovich, Itamar, 1942-